Winners are driven : - Unser, Bobby (J. Wiley, 2003)
This book depicts the life of Bobby Unser from his humble beginnings in the heartland to his many accomplishments. It spells out the philosophy of the great American spirit, the driving force of professional sports, and the necessity of having the presence of outstanding leaders and human beings throughout the world today